Patterns of Elementary School Students’ Bullying Victimization: Roles of Family and Individual Factors - Wu, Xinyue (Journal of interpersonal violence, 2023)
Physical, verbal, and relational bullying victimization are common forms of bullying victimization. Some victims may suffer only one form of victimization and some may suffer multiple forms of victimization at the same time. Bullying victimization groups are heterogeneous and different forms of victimization may have different combination patterns. Previous studies assessed patterns of bullying victimization among junior and senior high school students. However, limited studies explored patterns among elementary students and explored possible factors in shaping these patterns from the integrated perspective of family and individual. We expanded and deepened research in this area using questionnaires to collect self-report data for 866 parent/child pairs. Latent profile analysis was used to explore patterns of elementary students. Multinomial logistic regression was used to examine relations between patterns and family and individual factors. We found three bullying victimization groups: severe (5.4%), verbal (13.6%), and non-bullying victimization (81%). In family factors, the time parents spent with children was a protective factor for bullying victimization, and negative interactions with children was a risk factor. Individual-level protective factors for bullying victimization were coming from a single child household, positive coping style, and perceived peer support, whereas a negative coping style was a risk factor. These results indicate that different forms of bullying victimization co-occur among elementary school students. Some family and individual factors are associated with bullying victimization patterns. It is important to consider the heterogeneity among the bullying victimization groups of elementary students and influencing factors to develop targeted prevention interventions for different bullying victimization groups.